Effectiveness and Safety of iGlarLixi (Insulin Glargine 100 U/mL Plus Lixisenatide) in Type 2 Diabetes According to the Timing of Daily Administration: Data from the REALI Pooled Analysis - Haluzík, Martin; Seufert, Jochen; Guja, Cristian; Bonnemaire, Mireille; Bigot, Gregory; Tournay, Mathilde; Kis, János Tibor; Freemantle, Nick (Diabetes therapy, 2023)
INTRODUCTION: iGlarLixi (insulin glargine 100 U/mL plus lixisenatide) has demonstrated glycaemic efficacy and safety in adults with inadequately controlled type 2 diabetes mellitus (T2DM). Per the European Medicines Agency's product label, iGlarLixi should be injected once a day within 1 h prior to a meal, preferably the same meal every day when the most convenient meal has been chosen. It is however unknown whether iGlarLixi administration timing affects glycaemic control and safety, as clinical trial evidence is mainly based on pre-breakfast iGlarLixi administration. Therefore, we assessed the effectiveness and safety of iGlarLixi in clinical practice, according to its administration timing. METHODS: Data were pooled from two prospective observational studies including 1303 European participants with T2DM inadequately controlled on oral antidiabetic drugs with or without basal insulin who initiated iGlarLixi therapy for 24 weeks. Participants were classified into four subgroups based on daily timing of iGlarLixi injection: pre-breakfast (N = 436), pre-lunch (N = 262), pre-dinner (N = 399), and those who switched iGlarLixi injection time during the study (N = 206). RESULTS: No meaningful differences in baseline characteristics were observed between the study groups. Least-squares mean reductions in haemoglobin A1c (HbA1c) from baseline to week 24 were substantial in all groups, with the numerically largest decrease observed in the pre-breakfast group (1.57%) compared with the pre-lunch (1.27%), pre-dinner (1.42%), or changed injection time (1.33%) groups. Pre-breakfast iGlarLixi injection also resulted in a numerically greater proportion of participants achieving HbA1c < 7.0% at week 24 (33.7% versus 19.0% for pre-lunch, 25.6% pre-dinner, and 23.2% changed injection time). iGlarLixi was well tolerated across all groups, with low rates of gastrointestinal disorders and hypoglycaemia. Mean body weight decreased similarly in all groups (by 1.3-2.3 kg). CONCLUSION: iGlarLixi was effective and safe regardless of its daily administration time. However, pre-breakfast iGlarLixi injection resulted in a more effective glycaemic control.
Keywords: Insulin glargine; Type 2 diabetes; Fixed-ratio combination; Lixisenatide; Time of administration